2021
DOI: 10.3390/cancers13215370
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Z Gold Nanoparticles in Targeted Cancer Radiotherapy—Pharmacokinetic Modeling, Monte Carlo Simulation and Radiobiological Effect Modeling

Abstract: High-Z gold nanoparticles (AuNPs) conjugated to a targeting antibody can help to improve tumor control in radiotherapy while simultaneously minimizing radiotoxicity to adjacent healthy tissue. This paper summarizes the main findings of a joint research program which applied AuNP-conjugates in preclinical modeling of radiotherapy at the Klinikum rechts der Isar, Technical University of Munich and Helmholtz Zentrum München. A pharmacokinetic model of superparamagnetic iron oxide nanoparticles was developed in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 118 publications
(166 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, material that is specific cross sections for biopolymers [ 51 ] and for gold [ 143 , 144 ] that are used in nanodosimetry have already been developed and tested and they are soon going to be made available to the scientific community through Geant4-DNA. Especially, the cross sections for gold can contribute significantly to the gold nanoparticle-aided radiotherapy research [ 145 , 146 ]. The modeling of the chemical stage is currently being improved [ 133 ] and extended to longer times and macroscopic volumes [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, material that is specific cross sections for biopolymers [ 51 ] and for gold [ 143 , 144 ] that are used in nanodosimetry have already been developed and tested and they are soon going to be made available to the scientific community through Geant4-DNA. Especially, the cross sections for gold can contribute significantly to the gold nanoparticle-aided radiotherapy research [ 145 , 146 ]. The modeling of the chemical stage is currently being improved [ 133 ] and extended to longer times and macroscopic volumes [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous in-depth research of nanomaterials compared with traditional antitumor treatments, nanomaterials have been used in more and more clinical anticancer applications, showing great development potential [ 111 ]. For example, in our previous research, we found that some nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs), high-Z gold nanoparticles following intratumoral injection can provide a high local concentration of the agent, reduction of the particle clearance (i.e., renal or hepatic clearance) that increases the bioavailability of nanoparticles and has the effect of radiosensitizer in cancer radiotherapy, which can be used for long-term local anti-tumor therapy [ 112 , 113 ]. As an ideal anti-tumor drug candidate, copper-based nanomaterials have the following advantages: (i) compared with other metals, copper is cheap and rich in content [ 114 ], (ii) copper can induce reactive oxygen species (ROS)-mediated oxidative stress and promote tumor cell apoptosis [ 115 , 116 , 117 ], (iii) it has good biocompatibility, biodegradability, antibacterial properties, and selective cytotoxicity to cancer cells [ 118 ], and (iv) copper-based nanomaterials have less toxic effects on normal cells, fewer side effects, and are safer and more reliable [ 119 ].…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%
“…To evaluate the behavior of nanoparticles in vivo, we developed a pharmacokinetic model that mimics the uptake and distribution of AuNPs in mice. Multiscale Monte Carlo simulations were performed for AuNPs and SPIONs in tumor cells at the cellular and molecular levels to determine the increase in radiation dose and the formation of chemical radicals in the vicinity of AuNPs [ 17 ]. A biologically based mathematical model has been developed to predict the biological response of AuNPs to radiation amplification.…”
Section: Personalized Medicine In the Context Of The Development Of ...mentioning
confidence: 99%